The Unintended Consequences of the U.S. Adversarial Model in Latin American Crime (2020)
During the 1990s, Latin America experienced a criminal procedural revolution (LACPR) when approximately 70% of its countries abandoned their inquisitorial system and adopted the U.S. adversarial model. Following the LACPR, the region experienced a dramatic increase in crime, consolidating it as one of the most violent areas in the world. Despite previous empirical evidence indicating that procedural law affects criminal behavior, the effects of the LACPR continue highly unexplored. In this paper, we use the Latin American case to evaluate the impact of an adversarial reform on crime rates. Exploiting the quasi-experimental implementation of the reform in Colombia, we use an event study approach combined with differences-in-differences to estimate the reform’s effects on criminal activity. Despite the opposite incentives the reform created, we find an increase associated with the procedural transformation in overall crime rates (22%), violent crime (15%), and property crime (8%). We also observe a dramatic decrease in drug offenses associated with lower arrest rates. Our findings contribute to the literature on Latin American crime and the link between procedural law and criminal behavior.